A NiCo2S4@N/S–CeO2 composite as an electrocatalytic signal amplification label for aptasensing. Issue 42 (5th August 2020) - Li, Lele; Yang, Liwei; Zhang, Si; Sun, Yuping; Li, Fen; Qin, Tengteng; Liu, Xiaoqiang; Zhou, Yanmei; Alwarappan, Subbiah
Abstract : Herein, we designed a NiCo2 S4 @N/S–CeO2 composite with amplified electrocatalytic oxygen reduction (OR) capability by the in situ growth of NiCo2 S4 nanoparticles on CeO2 nanospheres with simultaneous doping of nitrogen and sulfur. Abstract : Herein, we designed a NiCo2 S4 @N/S–CeO2 composite with amplified electrocatalytic oxygen reduction (OR) capability by the in situ growth of NiCo2 S4 nanoparticles on CeO2 nanospheres with simultaneous doping of nitrogen and sulfur. After optical characterization of the composite, it was then employed as the signal amplification label for constructing an electrochemical aptasensor. The composite provides a biocompatible and large surface platform to load biomolecules and retain their bioactivity. More importantly, the composite shows a comparable electrocatalytic OR capability similar to a commercial Pt/C catalyst and far better than CeO2, attributed to the NiCo2 S4 deposition and oxygen vacancies introduced by N and S doping. Furthermore, the Koutecky–Levich plots indicate a nearly four-electron transfer pathway of the ORR. The as-prepared aptasensor exhibited a highly sensitive and selective determination of a model analyte-sulfadimethoxine with a wide linear range of 0.05–180 nM, a low detection limit of 0.02 ± 0.0011 nM and good feasibility for real-sample detection. This work paved an effective way for the design of highly efficient electrocatalysts with bright prospects in bioanalytical applications.